ANALYSIS OF THE OMNIBUS LAW ON JOB CREATION IN THE PERSPECTIVE OF SOCIOLOGY OF LAW - Mohammad Dimas Atmadja; Titi Yuliati; Upik Mutiara (Jurnal Hukum Replik, 2020)
One of the widely discussed issues is related to the implementation of the Omnibus Law on Job Creation. In the Omnibus Law, there are 3 patterns, namely "omnibus law which is a review of laws, regulations on new materials and the revocation of related regulations, as well as economic policy regulations." This study uses a normative approach with research results showing that the Omnibus Law in democratic societal change should lead to social happiness. So that the Omnibus Law needs to be analyzed in depth so as not to run away from the teachings of the sociology of law itself. Keywords: Omnibus Law, Job Creation, Sociology of Law